Phylogenetic relationship and taxonomic status of Gymnocypris eckloni (Schizothoracinae) based on specific locus amplified fragments sequencing - Wanghe, Kunyuan; Feng, Chenguang; Tang, Yongtao; Qi, Delin; Ahmad, Shahid; Nabi, Ghulam; Li, Xiaohui; Wang, Guojie; Jian, Longsheng; Liu, Sijia; Zhao, Kai; Tian, Fei (Frontiers in Ecology and Evolution, 2022)
Accurately delimiting phylogenetic relationships and taxonomic status is important for understanding species diversity and distributions and devising effective strategies for biodiversity conservation. However, species delimitation is controversial in Gymnocypris eckloni, a schizothoracine fish endemic to the Qinghai Tibetan Plateau. This study employs specific-locus amplified fragments sequencing (SLAF-seq) with comprehensively sampling of schizothoracine fishes to robustly identified the phylogeny of G. eckloni in the Yellow River (YR) population and Qaidam basin (QB) population. In total, 350,181,802 clean reads and 5,114,096 SNPs are identified from SLAF-seq. Phylogenetic analysis recovers a non-monophyletic population of G. eckloni between YR and QB populations, representing an independent phylogenetic relationship between the two populations. Species delimitation analyses by SNAPPER and GMYC methods using the genome-wide SNP data confirm that their taxonomic statuses are separated. This study highlights the importance of further reconsidering clearer taxonomy, which would improve the genetic diversity conservation of Tibetan highland fishes.